Age as a factor in sensory integration function in Taiwanese children [Corrigendum] - Lin CK (Dove Medical Press, 2013)
Lin CK, Wu HM, Wang HY, Tseng MH, Lin CH. Neuropsychiatric Disease and Treatment. 2013;9:995–1001.On page 997, second sentence of the Instrument section, reads "The TSIF subtests are as follows: (1) Postural Movement (12 items); (2) Bilateral Integration Sequences (16 items); (3) Sensory Discrimination (eleven items); (4) Sensory Modulation (21 items); (5) Sensory Seeking (nine items); (6) Attention And Activity Levels (18 items); and (7) Emotional Behavior (eleven items)." 22 should have been "The TSIF subtests are as follows: (1) Postural Movement (12 items); (2) Bilateral Integration Sequences (16 items); (3) Sensory Discrimination (eleven items); (4) Sensory Modulation (21 items); (5) Sensory Seeking (nine items); (6) Attention and Activity Levels (18 items); and (7) Emotional Behavior (eleven items)."22On page 997, fourth sentence of the Instrument section, reads "Teachers of the participants scored each behavior, as follows: 1 = never (the child never responds in this fashion when presented with the opportunity [0% of the time]); 2 = seldom (the child responds occasionally in this fashion [25%]); 3 = occasionally (the child responds sometimes [50%]); 4 = frequently [≥75%]; 5 = always (the child responds in the manner noted every time when presented with the opportunity [100%])." should have been "Teachers of the participants scored each behavior, as follows: 1 = never (the child never responds in this fashion when presented with the opportunity [0% of the time]); 2 = seldom (the child responds occasionally in this fashion [25%]); 3 = occasionally (the child responds sometimes [50%]); 4 = frequently [75%]; 5 = always (the child responds in the manner noted every time when presented with the opportunity [100%])."Read the original article